PENINGKATAN MUTU PEMBELAJARAN MELALUI PELATIHAN PENYUSUNAN INSTRUMEN HIGHER ORDER TIHINKING SKILL (HOTS) BAGI GURU PRODUKTIF SMK NEGERI DI JAKARTA TIMUR - Riyadi; Adi Tri Tyassmadi; Ratu Amilai Avianti; Anisa Cahyaningsih; Muh. Alvaritsi; M. Kevin (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract Our education is required to develop skills such as communication, collaboration, critical thinking, and creativity or which called “The 4Cs”. Teachers in Indonesia have met educational qualifications, but in pedagogic, professional, social, and personal competencies there are still many teachers who have not qualified yet, especially regarding the concept of learning which is often referred to as higher-order thinking skills or better known as Higher Order Thinking Skills (HOTS). The purpose of the article is to find out, provide an overview, and techniques for developing HOTS instruments for productive vocational school teachers in East Jakarta. The teacher of vocational school are expected to understanding and be able to develop HOTS-based assessment instruments. In this condition, it is necessary to provide training for productive teachers of SMK in improving the quality of learning through the preparation of HOTS-based assessment instruments. The method used in this article are by giving a lecture, doing the discussion, and giving online training using zoom meeting and google classroom which is attended by productive vocational teachers in East Jakarta. The training was given in 3 sessions, there are the presentation of HOTS-based learning planning materials, presenting HOTS-based assessment materials, and continued with training in developing HOTS-based assessment instruments. After the training was carried out, the participants were given a questionnaire to find out their general understanding of the HOTS assessment. The results show that 83.3% of respondents understand the concept of HOTS. By 76.7% of respondents stated that HOTS-based assessments have begun to be applied at the SMK level. While feedback on HOTS learning outcomes shows that 86.7% of respondents agreed that the school supported HOTS-based learning and assessments. In general, respondents (67%) were able to develop HOTS-based assessment instruments after attending the training. The impact of the results of this training is the availability of HOTS-based questions for vocational subjects that can measure the higher-order thinking skills of vocational students. Abstrak Dunia pendidikan kita dituntut untuk mengembangan ketrampilan seperti komunikasi, kolaborasi, berpikir kritis, dan kreativitas atau disebut dengan istilah 4Cs (Critical Thinking, Collaboration, Communication and Creativity). Guru di Indonesia telah memenuhi kualifikasi pendidikan, namun dalam kompetensi pedagogik, professional, sosial, dan kepribadian masih banyak guru yang belum mumpuni, apalagi terhadap konsep pembelajaran yang sering disebut sebagai kemampuan berpikir tingkat tinggi atau lebih dikenal dengan istilah Higher Order Thinking Skills (HOTS. Tujuan dari artikel untuk mengetahui, memberikan gambaran, dan teknik mengembangkan instrument HOTS bagi guru produktif SMK di Jakarta Timur. Diharapkan guru produktif SMK memahami dan mampu mengembangkan instrumen penilaian berbasis HOTS. Melihat kondisi demikian, maka diperlukan pelatihan bagi guru-guru produktif SMK dalam meningkatkan mutu pembelajaran melalui penyusunan instrumen penilaian berbasis HOTS. Metode yang digunakan adalah dengan ceramah dan diskusi serta praktik secara daring menggunakan zoom meeting dan google classroom yang diikuti oleh guru-guru Produktif SMK di Jakarta Timur. Pelatihan diberikan dalam 3 sesi, yaitu pemaparan materi perencanaan pembelajaran berbasis HOTS, penyampaian materi penilaian berbasis HOTS, diskusi, dan dilanjutkan dengan latihan menyusun instrumen penilaian berbasis HOTS. Setelah dilaksanakan pelatihan peserta diberikan kuesioner untuk mengetahui pemahaman secara umum terhadap penilaian HOTS. Hasilnya menunjukkan bahwa 83,3% responden memahami konsep dari HOTS. Sebesar 76,7% responden menyatakan penilaian berbasis HOTS sudah mulai diterapkan pada tingkat SMK. Sedangkan umpan balik hasil pembelajaran HOTS 86,7% responden setuju sekolah mendukung pembelajaran dan penilaian dilaksanakan berbasis HOTS. Secara umum responden (67%) mampu mengembangkan instrumen penilaian berbasis HOTS. Dampak yang ditimbulkan dari hasil pelatihan ini tersedianya soal-soal berbasis HOTS untuk mata pelajaran kejuruan yang dapat mengukur kemampuan berpikir tingkat tinggi siswa SMK.